Mesenchymal Stem Cells From Different Sources in Meniscus Repair and Regeneration - Ding, Guocheng; Du, Jianing; Hu, Xiaoqing; Ao, Yingfang (Frontiers in Bioengineering and Biotechnology, 2022)
Meniscus damage is a common trauma that often arises from sports injuries or menisci tissue degeneration. Current treatment methods focus on the repair, replacement, and regeneration of the meniscus to restore its original function. The advance of tissue engineering provides a novel approach to restore the unique structure of the meniscus. Recently, mesenchymal stem cells found in tissues including bone marrow, peripheral blood, fat, and articular cavity synovium have shown specific advantages in meniscus repair. Although various studies explore the use of stem cells in repairing meniscal injuries from different sources and demonstrate their potential for chondrogenic differentiation, their meniscal cartilage-forming properties are yet to be systematically compared. Therefore, this review aims to summarize and compare different sources of mesenchymal stem cells for meniscal repair and regeneration.